Um Olhar geográfico sobre as culturas afro-brasileira e indígena e suas territorialidades na Baixada Santista - Godoy, Thais Elis [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
We believe that the popular rites and demonstrations are languages of extreme importance for the construction of the the Brazilian people identity and cultural wealth. We also know that when it comes to african-Brazilian and/or indigenous culture, most has some prejudice, and is in the attempt to deconstruct such prejudices that our work develops, because we intend to approach such studied cultures to teachers daily lives, helping them in this deconstruction. We seek to score and produce a mapping of the major influence of indigenous and african-Brazilian cultural manifestations in some cities of the metropolitan area of Santos, Cubatao, Praia Grande, Santos and São Vicente. The importance of these events is confirmed when the National Artistic and Historic Heritage Institute (Iphan) becomes responsible along with the State and society by the calls intangible cultural heritage, which focuses our work, because we understand that both african-Brazilian and indigenous culture carries on the tradition of transmission of knowledge and techniques from generation to generation, appropriated, transformed and lived by each community and / or individual that feeds the sense of identity. Understanding that the politics of recognition, preservation and promotion of traditional Brazilian Cultures are new in the country, we tried to contribute to some memories and traditions are not lost in time and history of the Brazilian people

Acreditamos que as manifestações e ritos populares são linguagens de extrema importância para a construção da identidade do povo brasileiro e de sua riqueza cultural. Sabemos também que quando se trata de cultura afro-brasileira e/ou indígena muitos carregam certo preconceito. É na tentativa de descontruir tais preconceitos que nosso trabalho se desenvolve, pois pretendemos aproximar tais culturas estudadas do cotidiano de docentes - empoderando-os do assunto - e dos discentes, ajudando-os nessa desconstrução. Procuramos em alguns municípios da Região Metropolitana da Baixada Santista (Cubatão, Praia Grande, Santos e São Vicente) pontuar e produzir um mapeamento das principais manifestações culturais de influência indígena e afro-brasileira. A importância dessas manifestações é confirmada quando o Instituto do Patrimônio Histórico e Artístico Nacional (Iphan) torna-se responsável, em conjunto com Estado e sociedade, pelos chamados bens culturais imateriais, nos quais centra-se o nosso trabalho, pois entendemos que tanto a cultura indígena quanto afro-brasileira carregam a tradição da transmissão do conhecimento e de técnicas de geração em geração, apropriadas, transformadas e vivenciadas por cada comunidade e/ou indivíduo que alimenta o sentimento de identidade. Entendendo que as políticas de reconhecimento, preservação e valorização das Culturas Tradicionais Brasileiras são recentes no país, buscou-se contribuir para que algumas memórias e tradições não se perdessem no tempo e na história do povo brasileiro
Keywords: Cultura afro-brasileira; Indios; Baixada Santista (SP)